"The Best Minute and a Half of Audio": Boundary disputes and the Palin family brawl. (21st April 2018) - Schwartz, David Asa; Berkowitz, Dan
Abstract : In the introduction to a police audio recording of Bristol Palin describing her family's involvement in an Alaska house party brawl, CNN anchor Carol Costello commented: "This is quite possibly the best minute and a half of audio we've ever come across." The incident, however, involved an alleged assault—an act that mainstream journalism generally reports in a serious manner. Costello's glib treatment of the event could therefore be seen as potentially breaching the boundaries of professional practice, which brought a widespread media response from both mainstream organizations and right-leaning blogs. Through textual analysis of these items, this study illustrates the challenge of conducting media boundary work—and the role strain that results—when the subject of a story occupies space within both entertainment and news spheres.